2019
DOI: 10.3846/tede.2019.10291
|View full text |Cite
|
Sign up to set email alerts
|

Application of Population Evolvability in a Hyper-Heuristic for Dynamic Multi-Objective Optimization

Abstract: It is important to know the properties of an optimization problem and the difficulty an algorithm faces to solve it. Population evolvability obtains information related to both elements by analysing the probability of an algorithm to improve current solutions and the degree of those improvements. DPEM_HH is a dynamic multi-objective hyper-heuristic that uses low-level heuristic (LLH) selection methods that apply population evolvability. DPEM_HH uses dynamic multiobjective evolutionary algorithms (DMOEAs) as LL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…On the assumption of having established a minimum fitness as a stopping criterion, if no individual reached it, the process would be repeated using the new generation as the population, so that the fitness of the population would improve in successive generations. Macias-Escobar et al (2019) showed the effectiveness of population evolvability to solve dynamic optimization problems.…”
Section: Methodsmentioning
confidence: 99%
“…On the assumption of having established a minimum fitness as a stopping criterion, if no individual reached it, the process would be repeated using the new generation as the population, so that the fitness of the population would improve in successive generations. Macias-Escobar et al (2019) showed the effectiveness of population evolvability to solve dynamic optimization problems.…”
Section: Methodsmentioning
confidence: 99%
“…Many predictors benefit from the feature selection process since it reduces overfitting and improves accuracy, among other things (Chandrashekar and Sahin 2014). In the literature (Wang et al 2017;Macias-Escobar et al 2019), fitness landscape analysis has been shown to be an effective technique for analysing the hardness of an optimisation problem by extracting its features. Here, we review some existing approaches that are most closely related to the work proposed in this paper.…”
Section: Related Workmentioning
confidence: 99%
“…To avoid a computationally intensive operation, the work suggests that the number of sampled generations must be carefully defined. In Macias-Escobar et al (2019), a very similar approach has been proposed to apply population evolvability in a hyperheuristic, named Dynamic Population-Evolvability based Multiobjective Hyperheuristic. In Tan et al (2021), the authors proposed a differential evolution (DE) with an adaptive mutation operator based on fitness landscape, where a random forest based on fitness landscape is implemented for an adaptive mutation operator that selects DE's mutation strategy online.…”
Section: Related Workmentioning
confidence: 99%
“…Many predictors benefit from the feature selection process since it reduces overfitting and improves accuracy, among other things [2]. In the literature [23,12], fitness landscape analysis has been shown to be an effective technique for analysing the hardness of an optimization problem by extracting its features. Here, we review some existing approaches that are most closely related to the work proposed in this paper.…”
Section: Related Workmentioning
confidence: 99%
“…To avoid a computationally intensive operation, the work suggests that the number of sampled generations must be carefully defined. In [12], a very similar approach has been proposed to apply population evolvability in a hyper-heuristic, named Dynamic Population-Evolvability based Multi-objective Hyper-heuristic. In [21], the authors proposed a differential evolution (DE) with an adaptive mutation operator based on fitness landscape, where a random forest based on fitness landscape is implemented for an adaptive mutation operator that selects DE's mutation strategy online.…”
Section: Related Workmentioning
confidence: 99%